Incidence of Testicular abnormalities in Pigs reared under Field Conditions of Mizoram - KUMARESAN, A; PATHAK, K A; CHHETRI, BIJOY; AHMED, S K; DAS, ANUBRATA; BUJARBARUAH5, K M; PRASAD, H (The Indian Journal of Animal Reproduction, 2023)
Cases of testicular hypoplasia and epididymal cysts were recorded in Mizo local and Large White Yorkshire pigs. The incidence of rudimentary epididymal cysts was 0.14 per cent and was located at the caput region of testis. The cauda epididymal sperm concentration was much lower in the hypoplastic testes as compared to the normal testes.